A cultura organizacional e o sucesso da implantação e manutenção da manufatura enxuta: estudo de múltiplos casos em empresas industriais - Paoli, Filipe Marafon de (2015)
The publication of the MIT report (Massachusetts Institute of Technology), which was evidenced by the book "The Machine that Changed the World", contributed to several branches of industrial companies to be aware of lean manufacturing and what it represents. In Brazil, in particular, it has been observed in recent years a significant increase in the implementation of lean manufacturing in various sectors of industrial activity, as companies have joined the lean manufacturing to become more competitive in a scenario where increased productivity is required, using fewer resources. However, very often the lean manufacturing is implemented taking into consideration only the concept of their tools as a way to solve all the problems of an organization. In many cases they are not successful implementations due to various external factors of lean manufacturing are not considered. Is it possible to measure and compare the influence of organizational culture on the success of implementation and maintenance of lean manufacturing in industrial companies? Aiming to answer this question, this paper proposes the development of a study aiming to identify and determine the impact of organizational culture on the successful implementation of lean manufacturing. In order to verify that the industrial companies that have favorable organizational culture, ie, have greater success in the implementation and maintenance of lean manufacturing in their manufacturing processes, this paper to conducted a multiple case studies, in which six companies were analyzed in which it was investigated the existence of a relationship between the organizational culture characteristics and the success in the adoption of lean manufacturing. The results obtained enabled to conclude that companies having more favorable organizational culture had a more effective, complete and long lasting lean manufacturing implementation.